Hope for the Family: The Effects of College Costs on Maternal Labor Supply - Breno Braga; Olga Malkova (Institute of Labor Economics (IZA), 2020)
We examine the effects of college costs on the labor supply of mothers. Exploiting changes in college costs after the roll-out of nine generous state merit aid programs from 1993 to 2004, we analyze the difference in the labor supply of mothers before and after these programs were implemented. Mothers of college-age children decreased their annual hours of work after the start of a generous merit aid program, while fathers did not adjust their labor supply. There is no strong evidence that mothers changed their employment status, as most of the decrease in hours of work happened among employed mothers. Mothers of college-going children are entirely responsible for the decline in hours of work, where mothers of children who did not go to college experienced no change in hours of work. A 10 percent increase in spending on merit aid programs per undergraduate student leads to a 1.3 percent decline in hours of work among mothers of college-going children. The decline in labor supply is mainly due to adjustments among married, highly educated, and white mothers.
Keywords: I22; J22; J13; 330; college costs; maternal labor supply; state merit aid programs